Inflammation and heterogeneity in synucleinopathies - Freuchet, Antoine; Pinçon, Anaëlle; Sette, Alessandro; Lindestam Arlehamn, Cecilia S. (Frontiers in Immunology, 2024)
Neurodegenerative diseases represent a huge healthcare challenge which is predicted to increase with an aging population. Synucleinopathies, including Parkinson's disease (PD), dementia with Lewy bodies (DLB), and multiple system atrophy (MSA), present complex challenges in understanding their onset and progression. They are characterized by the abnormal aggregation of α-synuclein in the brain leading to neurodegeneration. Accumulating evidence supports the existence of distinct subtypes based on the site of α-synuclein aggregation initiation, genetics, and, more recently, neuroinflammation. Mediated by both central nervous system-resident cells, peripheral immune cells, and gut dysbiosis, neuroinflammation appears as a key process in the onset and progression of neuronal loss. Sex-based differences add another layer of complexity to synucleinopathies, influencing disease prevalence -with a known higher incidence of PD in males compared to females -as well as phenotype and immune responses. Biological sex affects neuroinflammatory pathways and the immune response, suggesting the need for sex-specific therapeutic strategies and biomarker identification. Here, we review the heterogeneity of synucleinopathies, describing the etiology, the mechanisms by which the inflammatory processes contribute to the pathology, and the consideration of sex-based differences to highlight the need for personalized therapeutics.